The effect of one and two sessions endurance and resistance exercise training per day on serum levels of IgA and cortisol in soccer players - Nabi Shamsaei; Hadi Abdi (فصلنامه ابن سینا)
Background and aims: Exercise can have a mutual effect on immune system function. Immunoglobulin levels fluctuate greatly during periods of stress, which are associated with elevated cortisol levels. The aim of current study was to investigate the effect of one and two bouts of selected training per day on IgA and cortisol serum levels in soccer players. Methods: Sixteen nonprofessional soccer players were randomly assigned to endurance and resistance exercise groups. First, the subjects performed single bout of exercise per day, then after a week of rest, they conducted two bouts of exercise per day. Blood samples were taken at four stages before and after exercise to measure the serum concentrations of IgA and cortisol. Results: IgA concentration increased non-significantly after a single bout of exercise, but it decreased after two bouts of exercise in both groups. This reduction was significant in the endurance group than the pretest (p<0.001). Cortisol concentration was almost unchanged after the single bout of exercise, but it increased after two bouts of exercise in both groups. These increases were significant in the endurance group (p<0.05). There was no significant difference between the two groups in the changes in serum cortisol and IgA. Conclusion: Doing more than one session of exercise per day, especially endurance activities, can possibly lead to decreased immune system function and increased catabolic status.